2011
DOI: 10.1038/nchem.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Jekyll-and-Hyde chemistry of Phaeobacter gallaeciensis

Abstract: Emiliania huxleyi, an environmentally important marine microalga, has a bloom- and-bust lifestyle in which massive algal blooms appear and fade. Phaeobacter gallaeciensis belongs to the roseobacter clade of α-Proteobacteria, whose populations wax and wane with that of E. huxleyi. Roseobacter are thought to promote algal growth by biosynthesizing and secreting antibiotics and growth stimulants (auxins). Here we show that P. gallaeciensis switches its secreted small molecule metabolism to the production of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
492
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(529 citation statements)
references
References 53 publications
16
492
1
2
Order By: Relevance
“…Although a variety of biotic and abiotic surfaces is colonized by P. gallaeciensis, some exceptions imply that some degree of host specificity exists. The type of microbe-host interaction of P. gallaeciensis may be mutualistic as well as pathogenic, as suggested by Seyedsayamdost et al (2011). The latter is supported by several virulenceassociated features like the type IV secretion system or siderophore production and was also stated for other marine bacteria (Thomas et al, 2008).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although a variety of biotic and abiotic surfaces is colonized by P. gallaeciensis, some exceptions imply that some degree of host specificity exists. The type of microbe-host interaction of P. gallaeciensis may be mutualistic as well as pathogenic, as suggested by Seyedsayamdost et al (2011). The latter is supported by several virulenceassociated features like the type IV secretion system or siderophore production and was also stated for other marine bacteria (Thomas et al, 2008).…”
Section: Discussionmentioning
confidence: 71%
“…Phenylacetyl-CoA as precursor for TDA biosynthesis and tropolone as an intermediate product in the TDA synthesis were both recently proposed as precursor of the newly discovered roseobacticides (Seyedsayamdost et al, 2011), which would link the synthesis of these secondary metabolites in P. gallaeciensis. The exact mechanism for the addition of sulfur to the TDA precursor has not been elucidated yet.…”
Section: Tda Biosynthesis In P Gallaeciensis Dsm 17395mentioning
confidence: 99%
See 1 more Smart Citation
“…The Roseobacter ‐clade bacteria are aerobic anoxygenic phototrophs (which also include Porphyrobacter ) that can use energy from light while growing on organic substances as carbon source (Koblížek, 2015). Members of this clade are reported to favour algal growth (Grossart and Simon, 2007; Seyedsayamdost et al ., 2011; Luo and Moran, 2014; Park et al ., 2017), although some representatives are able to turn the mutualistic relationship into a parasitic one, lysing algal cells to feed on the intracellular substances, when molecules signalling algal cell ageing are released (Seyedsayamdost et al ., 2011). A stimulating effect of the Roseobacter ‐clade representative Pelagibaca bermudensis on T. striata growth was reported under P‐limitation, possibly implying a P recycling activity of this bacterium (Park et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…R11, a variety of virulence factors were found including quorum sensing genes (Fernandes et al 2011). Several studies have shown members of the Roseobacter clade to be algacidal and opportunistically pathogenic (Amaro et al 2005;Imai et al 2006;Seyedsayamdost et al 2011). …”
Section: Discussionmentioning
confidence: 99%